DRA-net: A new deep learning framwork for non-intrusive load disaggregation - Yu, Fang; Wang, Zhihua; Zhang, Xiaodong; Xia, Min (Frontiers in Energy Research, 2023)
The non-intrusive load decomposition method helps users understand the current situation of electricity consumption and reduce energy consumption. Traditional methods based on deep learning are difficult to identify low usage appliances, and are prone to model degradation leading to insufficient classification capacity. To solve this problem, this paper proposes a dilated residual aggregation network to achieve non-intrusive load decomposition. First, the original power data is processed by difference to enhance the data expression ability. Secondly, the residual structure and dilated convolution are combined to realize the cross layer transmission of load characteristic information, and capture more long sequence content. Then, the feature enhancement module is proposed to recalibrate the local feature mapping, so as to enhance the learning ability of its own network for subtle features. Compared to traditional network models, the null-residual aggregated convolutional network model has the advantages of strong learning capability for fine load features and good generalisation performance, improving the accuracy of load decomposition. The experimental results on several datasets show that the network model has good generalization performance and improves the recognition accuracy of low usage appliances.